2021
DOI: 10.3390/ijms22115749
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Mesenchymal Stem Cells in the Rejuvenation of the Aging Immune System

Abstract: Rapid growth of the geriatric population has been made possible with advancements in pharmaceutical and health sciences. Hence, age-associated diseases are becoming more common. Aging encompasses deterioration of the immune system, known as immunosenescence. Dysregulation of the immune cell production, differentiation, and functioning lead to a chronic subclinical inflammatory state termed inflammaging. The hallmarks of the aging immune system are decreased naïve cells, increased memory cells, and increased se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 232 publications
(267 reference statements)
0
7
0
Order By: Relevance
“…As suggested by successful MSC use in a number of pathological scenarios involving uncontrolled immune activation with consequent tissue damage, like for example H9N2 induced acute lung injury, ARDS, autoimmune diseases and graft-versus-host disease ( Waterman et al, 2010 ; Elgaz et al, 2019 ; Coelho et al, 2020 ; Yen et al, 2020 ; Barros et al, 2021 ; Musial and Gorska-Ponikowska, 2021 ; Su et al, 2021 ), the undeniable immunomodulatory and inflammation relieving properties of MSCs make them putative candidates as rejuvenating factors for the older immune system, on the basis of the documented ability to reduce pro-inflammatory mediators and to promote the expansion of regulatory lymphocyte subsets ( Yeo et al, 2021 ). Also, MSC transplantation can contribute to the amelioration of aging frailty ( Schulman et al, 2018 ; Florea et al, 2019 ; Sun et al, 2019 ), but MSC may exhibit age related deteriorating functions linked to inflammageing, especially in terms of alterations in number and characteristics of extracellular vesicles, DAMP production, excessive IL-6 release, loss of MSC ability to shift monocyte polarization toward M2, and triggering of ineffective hemopoiesis ( Tsuruhara et al, 2017 ; Lee and Yu, 2020 ).…”
Section: Mesenchymal Stem Cell Transplantation In Covid-19 Patients: Rationale and Resultsmentioning
confidence: 99%
“…As suggested by successful MSC use in a number of pathological scenarios involving uncontrolled immune activation with consequent tissue damage, like for example H9N2 induced acute lung injury, ARDS, autoimmune diseases and graft-versus-host disease ( Waterman et al, 2010 ; Elgaz et al, 2019 ; Coelho et al, 2020 ; Yen et al, 2020 ; Barros et al, 2021 ; Musial and Gorska-Ponikowska, 2021 ; Su et al, 2021 ), the undeniable immunomodulatory and inflammation relieving properties of MSCs make them putative candidates as rejuvenating factors for the older immune system, on the basis of the documented ability to reduce pro-inflammatory mediators and to promote the expansion of regulatory lymphocyte subsets ( Yeo et al, 2021 ). Also, MSC transplantation can contribute to the amelioration of aging frailty ( Schulman et al, 2018 ; Florea et al, 2019 ; Sun et al, 2019 ), but MSC may exhibit age related deteriorating functions linked to inflammageing, especially in terms of alterations in number and characteristics of extracellular vesicles, DAMP production, excessive IL-6 release, loss of MSC ability to shift monocyte polarization toward M2, and triggering of ineffective hemopoiesis ( Tsuruhara et al, 2017 ; Lee and Yu, 2020 ).…”
Section: Mesenchymal Stem Cell Transplantation In Covid-19 Patients: Rationale and Resultsmentioning
confidence: 99%
“…In general, the above-mentioned mechanisms associated with senescence, such as the incessant oxidative stress, telomere shortening, impaired autophagy, or epigenetic alterations, impact both the innate and adaptative immune systems (reviewed by [ 23 ]). All of this has led to a line of evidence between the immune system and aging, which can be narrowed down to two categories, namely immunosenescence and inflamm-aging [ 24 ].…”
Section: Mechanisms Of Agingmentioning
confidence: 99%
“…The development of stem cell transplantation-based therapies to combat age-related functional decline has recently attracted considerable attention because of stem cells' potency to differentiate into and generate all cell types offers new opportunities for regenerative medicine and in fact, has been observed in various aged tissues. Stem cell genotypes exhibit an attenuated response to tissue damage, dysregulated proliferation and reduced regenerative potential (Yeo et al, 2021). Stem cell therapy is a recently emerged method for treating ovarian aging.…”
Section: Stem Cell Transplant Therapymentioning
confidence: 99%
“…Famous foreign scholars (Mohamed et al, 2018) proposed in 2018 that impaired reproductive performance can be treated by allogeneic bone marrow mesenchymal stem cell transplantation, which may be due to the immunogenicity of soluble drugs and cell contact and the secretion of growth factors and chemokines, to express extracellular matrix receptors on the surface of mesenchymal stem cells, thereby promoting the interaction between Research Progress on New Methods to Prevent and Treat Ovarian Senescence: A Review CXCR-4/SDF-1 and CD44 hyaluronic acid; this is achieved through the production of apoptosis-inhibiting molecules [such as vascular endothelial growth factor (VEGF) and transforming growth factor-β (TGF-β)] that help repair damaged tissue and promote angiogenesis, immunomodulation [such as interleukin-10 (IL-10) and interleukin-6 (IL-6)] and anti-inflammatory fibrosis, thereby exerting a therapeutic effect (Isik et al, 2017). Studies have shown that after systemic transplantation, BMSCs migrate to the injury site and play an immunomodulatory role, promoting tissue repair through growth factors and signaling molecules that guide the regeneration of resident tissue cells (Yeo et al, 2021;Jaiswal et al, 2020).…”
Section: Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%